2017
DOI: 10.31436/imjm.v16i1.358
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Anxiety and Sexual Dysfunction in Patients with Diabetes Mellitus With and Without Foot Ulcer

Abstract: Introduction: Anxiety and depression are both associated with increased morbidity in diabetic population, especially those afflicted with foot ulcer, whereas Erectile Dysfunction (“ED”) and Female Sexual Dysfunction (“FSD”) are amongst the common complication found in diabetes. This study aimed to determine the prevalence of anxiety and depression as primary outcome and sexual dysfunction (“SD”) as a secondary outcome in diabetic patients with and without foot ulcer (“DFU”). Methods: A cross-sectional study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…The existing literature is unanimous in reporting depression and anxiety as important variables that compromise QoL in these patients. 14,22 However, the present study showed how depression and anxiety together were associated with worse QoL and its domains using a specific DFUQoL scale. Overall, the results confirmed H1 and H2.…”
Section: Figure Clinically Significant Psychological Morbidity Modera...contrasting
confidence: 55%
See 4 more Smart Citations
“…The existing literature is unanimous in reporting depression and anxiety as important variables that compromise QoL in these patients. 14,22 However, the present study showed how depression and anxiety together were associated with worse QoL and its domains using a specific DFUQoL scale. Overall, the results confirmed H1 and H2.…”
Section: Figure Clinically Significant Psychological Morbidity Modera...contrasting
confidence: 55%
“…According to Alrub et al, 23 patients with DFUs report low DFUQoL because psychological distress is related to delayed healing and, consequently, long-term care, increasing the impact of DFU on day-to-day activities. The existing literature is unanimous in reporting depression and anxiety as important variables that compromise QoL in these patients 14,22 . However, the present study showed how depression and anxiety together were associated with worse QoL and its domains using a specific DFUQoL scale.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations